Blobitecture : waveform architecture and digital design - Waters, John K. (John Kevin) (Gloucester, Mass. : Rockport Publishers, 2003)
The Apple iMac; the new VW Beetle; the Oh Chair; the Guggenheim Bilbao museum. These are all classic examples of blobism, a futuristic retelling of the curve, resulting in protoplasmic forms designed by computers. A growing number of inventive architects are now embracing this concept, making "blobitecture" the hottest global trend in the industry. This title focuses exclusively on the phenomenon in detail: how the process works; the geometrics and environmental challenges it presents; the sophisticated software that allows artists to bend the lines of traditional architecture and the stunning work produced by this art form. Featuring curved walls to blob-esque furniture to Greg Lynn's Embryological House and Koloatan and McDonald's Title House, this is both a showcase of the best in blobism, illustrated through computer-drawn renderings, illustrations and photographs, and a guide to applying it in a designer's own work.
Birth of the blob -- Blob's your uncle -- New tools of the trade -- a blob by any other name -- Biological thinking -- An utterance without a language -- The poster boy" for blobism -- Outside the beige box -- Nex generation.
Includes bibliographical references (p. 174-181).
Keywords: Organic architecture -- Computer-aided design